The vital role of Gli1+ mesenchymal stem cells in tissue development and homeostasis. Issue 9 (2nd February 2021) - Jing, Dian; Li, Chaoyuan; Yao, Ke; Xie, Xudong; Wang, Peiqi; Zhao, Hu; Feng, Jian Q.; Zhao, Zhihe; Wu, Yafei; Wang, Jun
Abstract: The hedgehog (Hh) signaling pathway plays an essential role in both tissue development and homeostasis. Glioma‐associated oncogene homolog 1 (Gli1) is one of the vital transcriptional factors as well as the direct target gene in the Hh signaling pathway. The cells expressing the Gli1 gene (Gli1 + cells) have been identified as mesenchymal stem cells (MSCs) that are responsible for various tissue developments, homeostasis, and injury repair. This review outlines some recent discoveries on the crucial roles of Gli1 + MSCs in the development and homeostasis of varieties of hard and soft tissues. Abstract : The cells expressing the Gli1 gene (Gli1 + cells) have been identified as mesenchymal stem cells (MSCs) that are responsible for various tissue development, homeostasis, and injury repair. This review outlines some recent discoveries in the crucial roles of Gli1 + MSCs in the development and homeostasis of varieties of hard and soft tissues.